The role of environment-related and climate adaptation technologies in sustainable energy use: a dynamic quantile regression approach - Ismail Aremu Muhammed; Gamini Premaratne; Norulazidah H. Omar; Ahmed M. Khalid (Sustainable Futures, 2025)
The level of innovation in energy resources is critical to successfully implementing the de-carbonization agenda. However, despite growing investments and policy interventions, the effectiveness and impact of these technologies on sustainable energy consumption remain unclear, especially regarding the heterogeneity of this impact across different levels of energy sustainability. Therefore, this study examined the dynamic heterogeneous impact of green technologies on sustainable energy consumption. Specifically, it investigates how environment-related and climate change adaptation technologies influence renewable energy consumption and energy efficiency for 77 developed and developing countries between 1990 and 2021. The stochastic impacts by regression on population, affluence and technology (STIRPAT) framework served as the theoretical foundation for specifying the model. The method of moments quantile regression was employed with the inclusion of lagged dependent variables to account for dynamic heterogeneous impact. The findings revealed that environment-related technologies significantly promote renewable energy consumption, especially in developing countries. The positive influence of climate change adaptation technologies is limited to lower renewable energy quantiles. Moreover, environment-related technologies show some potential to reduce energy intensity, while climate change adaptation technologies worsen energy intensity. The findings are robust to alternative dynamic panel data estimators. The study suggests that policies promoting these environment-related technologies can boost energy sustainability, especially in developing countries. Furthermore, climate adaptation technologies have a limited impact on scaling renewable energy and energy efficiency. Thus, integrated policies aligning adaptation efforts with energy efficiency are essential for a balanced and sustainable transition.